2013
DOI: 10.1371/journal.pone.0052857
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practices of Diabetic Patients in the United Arab Emirates

Abstract: IntroductionDiabetes self-management education is a cornerstone of diabetes care. However, many diabetics in the United Arab Emirates (UAE) lack sufficient knowledge about their disease due to illiteracy. Thus, before considering any possible intervention it was imperative to assess present knowledge, attitudes, and practices of patients towards the management of diabetes.MethodsA random sample of 575 DM patients was selected from diabetes outpatient's clinics of Tawam and Al-Ain hospitals in Al-Ain city (UAE)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

60
196
16
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(302 citation statements)
references
References 17 publications
60
196
16
6
Order By: Relevance
“…Laboratory data were collected from each patient's electronic medical record (EMR). This cross-sectional study used a questionnaire known as the Michigan Brief Diabetes Knowledge Test to assess each patient's knowledge [7][8][9][10]. This questionnaire was also translated into Arabic.…”
Section: Methodsmentioning
confidence: 99%
“…Laboratory data were collected from each patient's electronic medical record (EMR). This cross-sectional study used a questionnaire known as the Michigan Brief Diabetes Knowledge Test to assess each patient's knowledge [7][8][9][10]. This questionnaire was also translated into Arabic.…”
Section: Methodsmentioning
confidence: 99%
“…In a study conducted in Thailand, knowledge about the illness were significantly related with the level of self-care behaviors [60,61]. In study conducted in Nigeria to evaluate the level of knowledge among type 2 diabetics showed that knowledge is below mean score 39% ± 16.7% [62].…”
Section: Idf Atlasmentioning
confidence: 96%
“…Number of days patient practiced specific behavior Self care behaviors mean score Total number of days under questions designed for that behavior = [9,48] and study done in JUSH, age is associated with self-care practices [40], study conducted in Thailand, age was an independent predictor of self-care practices [60] being young aged in Type 2 DM was associated with ability to shifting of view or mentality and motivation to engage in healthy lifestyles [91]. This could be attributed to lack of motivation and lack of social support in elderly individuals compared to young adults.…”
Section: Diabetes Knowledge Response Responsementioning
confidence: 99%
“…그런데 선행연 구에서 당뇨 지식과 자가간호행위가 상관관계가 있음을 보고 한 연구들이 있는 반면 (Al-Maskari et al, 2013;Choi & Jung, 2010;Tahmasebi, Noroozi, & Tavafian, 2013) 당뇨병 환자의 당뇨 지식과 자가간호행위가 유의한 상관관계가 없다고 보고 한 연구도 있다 (Lee, 2003;Xu, Toobert, Savage, Pan, & Whitmer, 2008). 또한 자가간호행위가 당뇨병 환자의 당화혈색소에 긍정적인 영향을 미칠 수 있고 (Al-Khawaldeh, Al-Hassan, & Froelicher, 2012;Park, 2010), 당뇨 지식 도 당화혈색소에 바람직한 결과를 제공하는 것으로 나타났으 나 (Lee, Kang, & Kim, 2008), 당화혈색소가 당뇨병 환자의 당 뇨 지식이나 자가간호행위와 유의하지 않다는 결과도 있었다 (Al-Maskari et al, 2013;Lee, 2003 • 대상자의 당뇨 지식, 자가간호행위와 당화혈색소 정도를 파 악한다.…”
unclassified